No Vacancy - Balchunas, Marius; Ricci, Christina; Lolita Davidovich; Rhona Bennett; Ryan Bollman; Timothy Olyphant; Olek Krupa (USA Lions Gate, 1999)
Lillian (Christina Ricci) is a 21-year-old drifter engaged to a philandering loser and locked in her room with a strange man. She lives next to a failed violinist who won't stop playing his instrument. He lives next to a New Age fanatic who's into colonic treatments; she lives next to two drug addicts who mess with the wrong prostitutes and end up answering to a pimp played by Robert Wagner. In a barrage of head-spinning vignettes, we are sucked into a surreal motel fantasy-land where society's riff raff dwell in that awkward place between freedom and desperation.
Lillian (Christina Ricci) is a 21-year-old drifter engaged to a philandering loser and locked in her room with a strange man...
Languages: English, Turkish Subtitle: Turkish
Keywords: Drama; Romance; Comedy